2017
DOI: 10.1097/md.0000000000007819
|View full text |Cite
|
Sign up to set email alerts
|

Two-stage hepatectomy for multiple giant alveolar echinococcosis

Abstract: Alveolar echinococcosis is a chronically progressive and potentially fatal disease. Patients with multiple giant alveolar echinococcosis have a poor prognosis when radical resection cannot be achieved, but curative resection can be limited by low future remnant liver volumes. In these cases, 2-stage liver resection may be a better choice: after a first-stage hepatectomy with partial resection, liver regeneration is allowed in the residual liver before proceeding to the second-stage hepatectomy. In this study, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 18 publications
0
5
0
Order By: Relevance
“…Surgical treatment is considered to ensure healing in the case of CE, because it completely removes the cause of the disease [26], but medical treatment must be associated with surgical therapy in order to prevent hydatid recurrence. When patients with CE cannot be operated on-either due to contraindications (e.g., associated diseases) or the locations being difficult to reach, the cysts being very small, or the presence of numerous tiny cysts-the only option is medical therapy [7,16,[21][22][23][24][25].…”
Section: Discussionmentioning
confidence: 99%
“…Surgical treatment is considered to ensure healing in the case of CE, because it completely removes the cause of the disease [26], but medical treatment must be associated with surgical therapy in order to prevent hydatid recurrence. When patients with CE cannot be operated on-either due to contraindications (e.g., associated diseases) or the locations being difficult to reach, the cysts being very small, or the presence of numerous tiny cysts-the only option is medical therapy [7,16,[21][22][23][24][25].…”
Section: Discussionmentioning
confidence: 99%
“…Previous literature has reported the use of PVE or TSH on patients suffering from hepatic AE with insufficient FLRV in a small sample size or in a limited form of case report. Shen et al have reported that seven patients with advanced multiple giant hepatic AE were treated through TSH, which effectively reduced the operation risk and achieved radical resection [ 43 ]. Similarly, these seven patients had at least two lesions and the FLRV was less than 30% of the total liver volume.…”
Section: Discussionmentioning
confidence: 99%
“…Gruttadauria et al indicated postoperative liver failure after hepatic resection for patients is highly occurred when the RLV less than 30% (45). Based on this index (RLV =30%), Shen et al made the surgical plan as whether resect the lesions in one stage or not for multiple giant HAE patients (46). Based on the author's experience, the RLV should be more than 30% for "health" liver before ERAT.…”
Section: Preoperative Managementmentioning
confidence: 99%